2020
DOI: 10.1016/s2589-7500(20)30165-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human mobility restrictions on the spread of COVID-19 in Shenzhen, China: a modelling study using mobile phone data

Abstract: Summary Background Restricting human mobility is an effective strategy used to control disease spread. However, whether mobility restriction is a proportional response to control the ongoing COVID-19 pandemic is unclear. We aimed to develop a model that can quantify the potential effects of various intracity mobility restrictions on the spread of COVID-19. Methods In this modelling study, we used anonymous and aggregated mobile phone sightings data to build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
246
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(260 citation statements)
references
References 21 publications
10
246
0
4
Order By: Relevance
“…For example, they also unexpectedly experienced a serious COVID-19 pandemic (news.china.com.cn), which may be attributed to the tourists coming from Wuhan, and some of them have carried the SARS-CoV-2 virus [20]. Population migration is closely related to the deterioration of pandemic, and it is a harbinger of the future situation of epidemics [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they also unexpectedly experienced a serious COVID-19 pandemic (news.china.com.cn), which may be attributed to the tourists coming from Wuhan, and some of them have carried the SARS-CoV-2 virus [20]. Population migration is closely related to the deterioration of pandemic, and it is a harbinger of the future situation of epidemics [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Because COVID-19 has an incubation period of even more than 40 days, these people outflow from Wuhan could cause community-level infections in other cities. Timely travel restrictions have weakened the spread of the pandemic [22,23]. Population social gathering together with the infection source from exposure in Wuhan has occurred in many cities such as Tianjin, Beijing and Chengdu, which was an essential cause leading to the rapid deterioration of the COVID-19.…”
Section: Plos Onementioning
confidence: 99%
“…For example, Wells and Sah [12] examined the influence of cross-national travel and border-control policies on the spread of COVID-19 at a global level. Zhou and Xu [13] used mobile phone sightings data to examine the potential effects of intra-city mobility restrictions on the spread of COVID-19 in the city of Shenzhen. Massaro and Kondor [14] studied the interaction between human mobility and outbreaks of infectious diseases and found that intra-city human mobility is a major factor in the spread of infectious diseases in Singapore.…”
Section: Human Mobility and Infectious Diseasesmentioning
confidence: 99%
“…Adherence to “stay at home” directives can be inferred from mobility data retrieved from mobile phones. These data can be used to test whether, at group level, people’s mobility behaviour changes as a function of the social (physical) distancing guidelines [ 32 ]. However, for other types of protective measures such data are not publicly available because they concern intimate aspects of people’s personal lives.…”
Section: Introductionmentioning
confidence: 99%